Emergent Multifunctional Magnetic Proximity in van der Waals Layered Heterostructures. Issue 21 (21st May 2022) - Choi, Eun‐Mi; Sim, Kyung Ik; Burch, Kenneth S.; Lee, Young Hee
Abstract: Proximity effect, which is the coupling between distinct order parameters across interfaces of heterostructures, has attracted immense interest owing to the customizable multifunctionalities of diverse 3D materials. This facilitates various physical phenomena, such as spin order, charge transfer, spin torque, spin density wave, spin current, skyrmions, and Majorana fermions. These exotic physics play important roles for future spintronic applications. Nevertheless, several fundamental challenges remain for effective applications: unavoidable disorder and lattice mismatch limits in the growth process, short characteristic length of proximity, magnetic fluctuation in ultrathin films, and relatively weak spin–orbit coupling (SOC). Meanwhile, the extensive library of atomically thin, 2D van der Waals (vdW) layered materials, with unique characteristics such as strong SOC, magnetic anisotropy, and ultraclean surfaces, offers many opportunities to tailor versatile and more effective functionalities through proximity effects. Here, this paper focuses on magnetic proximity, i.e., proximitized magnetism and reviews the engineering of magnetism‐related functionalities in 2D vdW layered heterostructures for next‐generation electronic and spintronic devices. The essential factors of magnetism and interfacial engineering induced by magnetic layers are studied. The current limitations and future challenges associated with magnetic proximity‐related physics phenomena in 2D heterostructures are further discussed. Abstract : Beyond the conventional magnetic proximity effect, a much broader picture of magnetic proximity effects to control the material functionalities suggests a ubiquitous approach to transform a wide class of materials. Since the discovery of huge library of two‐dimensional materials, magnetic proximity effect is extensively investigated to attain intrinsic spin‐dependent properties from its adjacent for next‐generation electronic and spintronic devices.